The Implementation of Diversion in Handling of Criminal Actions Performed by Child - Anak Agung Putra Dwipayana; Jawade Hafidz; Aryani Witasari (Law Development Journal, 2022)
The purpose of this study was to obtain and find out information data about the implementation of diversion in handling criminal acts committed by children. The method used by the researcher was legal approach normative juridical and the specifications in this study were descriptive. The sources and types of data in this study are secondary data obtained from literature studies which were analyzed qualitatively. Based on the results of the study that implementation of diversion in handling criminal acts committed by children carried out by investigators, especially at the investigation stage, namely investigators have carried out law enforcement properly by receiving and serving every report or complaint given by the community and perpetrators by always fulfilling the rights of victims and suspects in order to provide a sense of justice for both the suspect and the victim. The obstacles include legal regulations and their handling procedures that do not support criminal acts committed by children with mental disorders. Law enforcers, in this case child investigators, are still lacking both in terms of the number of investigators and the level of knowledge of investigators in handling child crimes. There is no Temporary Child Placement Institution (LPAS) as mandated in Act No. 11 of 2012. The effort is to carry out the stages of the investigation in accordance with the SOP accompanied by asking for advice and input from prosecutors and experts. Request an increase in the number of personnel and carry out training and vocational education for personnel as well as carry out sharing and brainstorming with the Prosecutor's Office. Coordinate with the Social Service to facilitate child offenders who do not have parents or a place to live.